Training needs analysis (TNA) practices : a survey of the top 1000 corporate companies in Malaysia - Jamil, Rossilah (Universiti Teknologi Malaysia, 2005)
The literature of training strongly suggests that any training intervention must be preceded with the process of training needs analysis (TNA). This prerequisite step is considered important in providing organizations with valuable information to help them in designing strategic training programs. The manner to which TNA is approached is also important in determining the accuracy of its results. Existing literature on TNA shows that most studies on organizational TNA practices were done overseas. Due to various cultural and national differences, these findings may not reflect similar descriptions regarding TNA practiced in this country. With regard to these, this research was carried out with the purpose of understanding how organizations in Malaysia practice their TNAs. The research looked into many aspects such as nature of training needs commonly offered by organizations, individuals involved in selecting training participants, data collection methods and techniques used to perform TNA process, and also general perspectives regarding organizational TNA practices. Comparisons of TNA practices between organizations of different demographic backgrounds were also studied to see any differences in commitment towards TNA. Survey questionnaires were mailed to 278 companies listed in the top 1000 companies in Malaysia as in the directory of Malaysia 1000 (2003). Data was analyzed using various statistical methods including descriptive statistical technique, Kruskall-Wallis, Mann-Whitney, Spearman and Pearson Correlations. Based on 30% rate of returns, results of the research showed that the top 1000 corporate companies' approaches to TNA were quite systematic and in accordance with the suggestions in the literature. However, their approaches may not be sophisticated. The research found no significant differences in TNA practices of organizations of most demographic characteristics. However, companies of dissimilar nationality of parent companies were significantly different in terms of delivery of soft skill training, use of questionnaire and advisory committe as data collection methods, and use of competency analysis technique. The application of SWOT, competency analysis and managerial skills audit techniques were also different betwwen organizations with and without a training unit. ISO certification of firms was found to correlate with the firms' use of performance appraisal method and critical incident technique, though the relationships for both were very weak. Relationships were found between firms' length of operations with two data collection methods namely SKAs tests (weak) and Delphi(very weak). Very weak relationships were also found between length of operations and application of several techniques like organizational scanning, task / KSA analysis, competency analysis, skills inventory, managerial skills audit, performance review, versatility chart / analysis and critical incident technique. Finally, in correspondence with previous research, the study found a relationship between size of firm of training budget although the correlation value was low. The literature of training strongly suggests that any training intervention must be preceded with the process of training needs analysis (TNA). This prerequisite step is considered important in providing organizations with valuable information to help them in designing strategic training programs. The manner to which TNA is approached is also important in determining the accuracy of its results. Existing literature on TNA shows that most studies on organizational TNA practices were done overseas. Due to various cultural and national differences, these findings may not reflect similar descriptions regarding TNA practiced in this country. With regard to these, this research was carried out with the purpose of understanding how organizations in Malaysia practice their TNAs. The research looked into many aspects such as nature of training needs commonly offered by organizations, individuals involved in selecting training participants, data collection methods and techniques used to perform TNA process, and also general perspectives regarding organizational TNA practices. Comparisons of TNA practices between organizations of different demographic backgrounds were also studied to see any differences in commitment towards TNA. Survey questionnaires were mailed to 278 companies listed in the top 1000 companies in Malaysia as in the directory of Malaysia 1000 (2003). Data was analyzed using various statistical methods including descriptive statistical technique, Kruskall-Wallis, Mann-Whitney, Spearman and Pearson Correlations. Based on 30% rate of returns, results of the research showed that the top 1000 corporate companies' approaches to TNA were quite systematic and in accordance with the suggestions in the literature. However, their approaches may not be sophisticated. The research found no significant differences in TNA practices of organizations of most demographic characteristics. However, companies of dissimilar nationality of parent companies were significantly different in terms of delivery of soft skill training, use of questionnaire and advisory committe as data collection methods, and use of competency analysis technique. The application of SWOT, competency analysis and managerial skills audit techniques were also different betwwen organizations with and without a training unit. ISO certification of firms was found to correlate with the firms' use of performance appraisal method and critical incident technique, though the relationships for both were very weak. Relationships were found between firms' length of operations with two data collection methods namely SKAs tests (weak) and Delphi(very weak). Very weak relationships were also found between length of operations and application of several techniques like organizational scanning, task / KSA analysis, competency analysis, skills inventory, managerial skills audit, performance review, versatility chart / analysis and critical incident technique. Finally, in correspondence with previous research, the study found a relationship between size of firm of training budget although the correlation value was low.